2021
DOI: 10.3390/antibiotics10030255
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Antibiotic Resistance Genes and Susceptibility to Antibiotics among the Carbapenem-Resistant Gram-Negative Pathogens

Abstract: In this study, the correlation between the antibiotic resistance genes and antibiotic susceptibility among the carbapenem-resistant Gram-negative pathogens (CRGNPs) recovered from patients diagnosed with acute pneumonia in Egypt was found. A total of 194 isolates including Klebsiella pneumoniae (89; 46%), Escherichia coli (47; 24%) and Pseudomonas aeruginosa (58; 30%) were recovered. Of these, 34 (18%) isolates were multiple drug resistant (MDR) and carbapenem resistant. For the K. pneumoniae MDR isolates (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 69 publications
1
12
0
Order By: Relevance
“…Similar high-prevalence rates of MDR E. coli have been recently reported by other researchers across several Egyptian governorates. In Cairo, Abdelaziz et al and Abdelkhalik et al reported MDR E. coli rates reaching 60% and 80%, respectively [ 17 , 18 ]. In the Upper Egypt sector, Masoud et al identified a frequency of 73% [ 3 ], and at northeastern part of Egypt, Zagazig, El-Sokkary et al observed a MDR pattern among 87.5% of E. coli isolates [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar high-prevalence rates of MDR E. coli have been recently reported by other researchers across several Egyptian governorates. In Cairo, Abdelaziz et al and Abdelkhalik et al reported MDR E. coli rates reaching 60% and 80%, respectively [ 17 , 18 ]. In the Upper Egypt sector, Masoud et al identified a frequency of 73% [ 3 ], and at northeastern part of Egypt, Zagazig, El-Sokkary et al observed a MDR pattern among 87.5% of E. coli isolates [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the emergence of carbapenem-resistant E. coli isolates is already being noted. The carbapenem-resistant E. coli , along with other members of Enterobacteriaceae family, are often quoted as “nightmare bacteria” due to their ability to thrive in healthcare facilities and to spread to patients as well as to the surrounding environment, thus jeopardizing the last treatment alternative reserved for these MDR bacteria [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some ARGs detected in this experiment, such as RanA and RanB , showed a level of agreement with antibiotic resistance higher than 90%, whereas the kappa value was lower than 0.1, showing poor agreement. Abdelaziz et al (2021) used Pearson chi square to calculate the association between the phenotype of antibiotic resistance and the resistance genes, and found that the blaSHV and MexA genes were significantly associated with resistance to fluoroquinolones, amikacin, tobramycin, cotrimoxazole, and β-lactams other than aminoglutethimide. Kumburu et al (2019) calculated the kappa values for cefazolin, ceftazidime, ceftriaxone, chloramphenicol, ciprofloxacin, gentamicin, nalidixic acid, and ampicillin, with corresponding resistance genes with kappa values ranging between 0.05 and 1, indicating slight to complete concordance.…”
Section: Discussionmentioning
confidence: 99%
“…The high priority category includes bacteria such as Enterococcus faecium and Staphylococcus aureus that are resistant to various antibiotics, such as vancomycin and fluoroquinolones. The medium priority category includes bacteria such as Streptococcus pneumoniae and Shigella that, although they may have some resistance, effective antibiotics are still available that can kill them [9,11].…”
Section: Introductionmentioning
confidence: 99%